Host Microbiota Influences Interactions Between Hosts And Pathogens - Eppler, Megan E.; Grimes, Elizabeth A.; Hedden, Emily S.; Hodoameda, Peter; Hughes, Jamie M.; Isle, Kristin C.; Jojola-Mount, Valerie B.; Mason, Lindsay M.; Michel, Kristin; Viteri, Bianca Morejon; Ngwaga, Tshegofatso; Platt; et al. (My University, 2020)
Bacterial microbiota have significant effects on host interactions with pathogens in both vertebrate and invertebrate organisms. Here we discuss the direct and indirect impacts of microbiota on defense against pathogens. We found that microbiota have direct effects on host defense against pathogens through interference and niche competition, and by influencing host immune system development and function. The host microbiota also impacts host-pathogen interactions beyond immunity, by influencing physical barriers and physiological responses. In addition, it can influence the establishment of tumorigenic microbes thereby increasing cancer risk. Thus, the relationship between the host and its microbiota has short- and long-term impacts on overall health. Research that aims to identify and characterize the mechanisms that underlie these direct and indirect effects on host health will inform future medical treatments.
This manuscript is the product of the graduate class BIOL890B: Host-Pathogen Interactions, which was taught Fall 2020 at Kansas State University. All students in the class share authorship equally and are listed in alphabetical order by last name in alphabetical order. This course was co-taught by Dr. Kristin Michel (kmichel@ksu.edu) and Dr. Thomas Platt (tgplatt@ksu.edu), who serve as corresponding authors for this manuscript.